2021
DOI: 10.1038/s41422-021-00531-8
|View full text |Cite|
|
Sign up to set email alerts
|

Interferon-armed RBD dimer enhances the immunogenicity of RBD for sterilizing immunity against SARS-CoV-2

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a global crisis, urgently necessitating the development of safe, efficacious, convenient-to-store, and low-cost vaccine options. A major challenge is that the receptor-binding domain (RBD)-only vaccine fails to trigger long-lasting protective immunity if used alone for vaccination. To enhance antigen processing and cross-presentation in draining lymph nodes (DLNs), we developed an interferon (IFN)-armed RBD dimerized by an immunoglobulin f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 56 publications
0
44
0
Order By: Relevance
“…Preclinical studies have evaluated the protective efficacy of several RBD-specific monoclonals, as well as RBD as a protective immunogen. Investigators evaluating RBD as a vaccine candidate have delivered the antigen either as DNA 81 , mRNA 7,74,[82][83][84][85] , viral vector 86 , soluble monomer or dimer 6,22,[87][88][89][90][91][92][93] , a fusion protein nanoparticle 16,26,[94][95][96][97][98] , or as a virus-like particle (VLP) 91,[99][100][101][102] . Additional RBD-based vaccine candidates in clinical trials (Table 2)…”
Section: Preclinical Studies Support Rbd As a Potent Vaccine Antigenmentioning
confidence: 99%
“…Preclinical studies have evaluated the protective efficacy of several RBD-specific monoclonals, as well as RBD as a protective immunogen. Investigators evaluating RBD as a vaccine candidate have delivered the antigen either as DNA 81 , mRNA 7,74,[82][83][84][85] , viral vector 86 , soluble monomer or dimer 6,22,[87][88][89][90][91][92][93] , a fusion protein nanoparticle 16,26,[94][95][96][97][98] , or as a virus-like particle (VLP) 91,[99][100][101][102] . Additional RBD-based vaccine candidates in clinical trials (Table 2)…”
Section: Preclinical Studies Support Rbd As a Potent Vaccine Antigenmentioning
confidence: 99%
“…Previously, Sun et al constructed an interferon-armed RBD dimer vaccine inducing the production of high titers of long-lasting nAbs in mice and rhesus macaques [ 6 ]. Here, we acquired three kinds of RBD dimer vaccines carrying WT, Beta, and Delta RBD proteins from the Peng group (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…1 Potent and broad neutralization against SARS-CoV-2 variants elicited by sequential immunization with a wild-type inactivated vaccine and a mutant RBD subunit vaccine in mice. a Schematic diagram of the RBD dimer vaccine named I-P-R-F [ 6 ]. The structural elements show IFNα, Pan-DR epitope (PADRE), RBD, and immunoglobulin Fc fragment.…”
Section: Main Textmentioning
confidence: 99%
“…While RBD+Alum induces significant immune responses, it has been suggested that its immunogenicity should be increased. Different approaches have been proposed to increase its immunogenicity, such as i) expression as dimer 42,48,65,67 or trimers 44 , ii) fusion to carrier proteins like human IgG Fc moiety 43,67 , tetanus toxoid 11 , interferon-α 67 , iii) addition of pan HLA-DR-binding epitope to enhance helper T cell responses 67 , iv) using nanoparticles as delivery system 41,45,47,52,59 or v) addition of immunopotentiators as CpG 41,42,46,59 , MPLA 43 , 3M-052 or a TLR-7/8 agonist 44,59 .…”
Section: Discussionmentioning
confidence: 99%